(untitled) (British Journal of Global Ecology and Sustainable Development, 2022)
This article reviews the strategic management of innovation processes and develops the scheme for formation of mechanisms of innovation strategies of the enterprise. It is substantiated that innovation strategy is the factor and main condition for competitive development of an enterprise.